(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Background: World Health Organization (WHO) defines unsafe abortion as a procedure for terminating an unintended pregnancy either by individuals without the necessary skills or in an environment that does not conform to minimum medical standards, or both. Unsafe abortion has been attributed to 4.7 to 13.2% of maternal deaths each year and about 7 million women are reportedly admitted to the hospitals following unsafe abortion every year in the developing countries. This study aims to analyze the most frequently occurring complications and maternal outcomes due to unsafe termination of pregnancy (abortions and miscarriage) in patients presented at a tertiary care setting. Patients and Methods: A total of 30 patients admitted with complications due to unsafe termination of pregnancy were evaluated. The study was conducted at the emergency of Obstetrics and Gynecology department, General Hospital, Lahore from November 2016 till November 2017. Data was collected prospectively from patients through a performa containing basic demographic and unsafe abortion-related questions after their informed consent. Results: Mean age of the patients was 30.6±6.46 years while gestational age was 8.3±2.74 weeks. Almost all patients, 29 (96.7%) out of 30 were married. A majority (73%) of women had high parity. More than 90% women had also the history of previous abortions; however, only 5 (16.7%) had the history of unsafe abortions out of total sample. Dai’s were the most preferred service provider for this type of abortion and used home environment for abortions. Retained products of conception (RPOC), uterine perforation, endometritis, and septicemia were most common complications. All patients had received the antibiotics while 28 (93.3%) patients received the blood transfusion. Only 2 (6%) patients had received hysterectomy treatment for complications of unsafe abortion. Three patients (10%) maternal deaths were also recorded. Conclusion: This study concludes that unskilled service providers are still common abortionists in the community. Likewise, considerable maternal deaths are still waiting to deal with. Government institution and community awareness integrated model can reduce this problem and its impact on the health care system and women health as well.